PENINGKATAN HASIL PEMBELAJARAN GERAK DASAR CHEST PASS DALAM PERMAINAN BOLABASKET MELALUI MEDIA BOLA KARET (PENTUL) - Denny Afrizal Kameswara; Hasan Basri (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2020)
The research was conducted at SDN Tugu Utara 13 Pagi, which determined that the subjects of all students were 32 people, from class V Odd Semester of the 2018/2019 Academic Year. The research time was carried out for three months. With the frequency of learning two (2) times a week by means of face to face meeting in a structured manner. The meeting was held from July to September 2018. The research method used was action research, with the design model of Kemmis and Taggart. Overall data in the form of quantitative data were analyzed descriptively, there was an increase in student learning outcomes from pre-cycle to cycle 1 then cycle 2 in the form of learning outcome test scores, among others: 1) Data in Pre-cycle, the average score of the test of the chest basic motion technique ability test. The pass in the pre-cycle is 67.2, the percentage of students who have completed = 7/32 = 0.22 x 100% = 21.87%, the percentage of students who have not completed = 25/32 = 0.78 x 100% = 78.13 %. 2) Data in Cycle I, the average score of the basic chest pass technique test in cycle I was 72.25, the percentage of students who completed = 14/32 = 0.43 x 100% = 43.75%, 3) Data in Cycle II, the average score of the chest pass basic motion technical test test in cycle 2 through modified rubber balls, namely 77.77, the percentage of students who completed = 27/32 = 0.84 x 100% = 84.37 %.